Methodological questions of a survey of civil organizations - Pierog , Anita; Szabados , György Norbert (Applied Studies in Agribusiness and Commerce, 2012)
Today, the non-profit sector, and especially the role of civil organizations, has become significant in society. In Hungary there has been a large development in the past 20 years, in the non-profit sector, as the number of such organizations has quadrupled. The number of classic civil organizations (foundations and associations) makes up more than 80% of the non-profit sector. The social attendance, economic significance and affect often raise the issue of the true intensity of the sphere and also the question of why there are such vast differences between the conditions of function, human resources and how successful they are. For years now, with management related examination, we have been searching for the answers to the above questions, within the confines of the functional aspect research program of the Institute of Management and Organization in University of Debrecen, Centre for Agricultural and Applied Economic Sciences, Faculty of Applied Economics and Rural Development. Above all, we made an attempt to find general, management- related results and answers, with the use of probability sampling, a low number of samples and surveying. In the selection process of organizations to include in our research, we relied on the data base of the Court of Hajdú-Bihar County and with K-aspect systematic sampling, and we also questioned more than 140 managers from different organizations. With this research, we acquired a diverse collection of information, which now we intend to summarize within this article. With this article, we aim to find out how realistic a picture the database of the Court gives regarding the civil activity of the county. Even the sampling was not trouble free, since the entire database is not accessible. The survey also revealed some problems that confirmed the statement of the Central Statistic Office (KSH), i.e. that some organizations either do not function at all or function in name only.